BIBLIOMETRIC ANALYSIS OF ZAKAT RESEARCH FOR SUPPORTING SDGS - Rosyidi, Luthfi Nur; Sukmaningrum, Puji Sucia; Widiastuti, Tika (Universitas Airlangga, 2024)
Introduction: This research aims to reveal and map the publication regarding zakat to achieve SDGs. Methods: Based on the Scopus database, this study attempts to present an overview of papers, authors, journals, and countries that are prominent in zakat research using the bibliometric technique. Results: Until November 2022, there were 618 documents published by 1,356 authors. And zakat-related research has increased over the last 14 years, with Malaysia having the most authors publishing articles in the field of zakat. Non-Muslim countries, such as the United States, are also included on the list. The research findings show that there are seven pillars in zakat research: pillar 1 (No Poverty), pillar 2 (Zero Hunger), pillar 3 (Good Health & Well-being), pillar 4 (Quality Education), pillar 8 (Decent Work & Economic Growth), pillar 9 (Industry, Innovation, and Infrastructure), and pillar 10 (Industry, Innovation, and Infrastructure). These pillars correspond to the goal of zakat, which is to distribute wealth for the benefit of the people. Conclusion and suggestion: The government is expected to implement regulations and use existing models to optimize zakat to improve SDG achievement. This research can also be used as a guideline for future research by academics based on the trend and the gap research found in this study.